Knowledge and Awareness of Various Dental Biomaterials Used In Pediatric Patients - A Survey - Aleena Alex1, Balaji Ganesh S2 , Lavanya Prathap3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Restoration of decayed primary teeth is important and significant for proper maintenance of child healthand also for the development of their teeth. The materials preferred for restoration are composite, glassionomer, compomer, resin modified glass ionomer cement, stainless steel crown. Therefore it is importantto have knowledge about materials and its uses which makes the durability of restoration longer. The aimof the study is to assess the knowledge and awareness of various dental biomaterials used in pediatricpatients among the undergraduate dental students. A questionnaire of 12 questions based on different dentalbiomaterials used in pediatric patients was prepared and it responded by 140 students. Data was collectedand with the help of SPSS software data was analysed. Only 9% of students were aware that pit and fissuresealants are bound to tooth surface by both chemical and mechanical bonding. Only 33% opted correctlythat stainless steel crowns are semi permanent restorations. Amalgam was the most used restorative materialin primary molar by both the male and female students. The material of choice for restoring primary molarswith proximal caries and in multi surface carious lesions is glass ionomer cement. The students consideredease of manipulation and durability of the restorative material while selecting it for use in pediatric cases.Within the limitations of this survey, it can be concluded that the participants have an average level ofknowledge about various dental biomaterials used in pediatric patients.